2011
DOI: 10.1111/j.1939-165x.2011.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of dog erythrocyte antigen 1.1 in 4 breeds native to different areas inTurkey

Abstract: The frequency of DEA 1.1-positive dogs among 4 Turkish breeds is high compared with that of most other breeds previously surveyed. The predicted risk of both sensitization and occurrence of DEA 1.1-related HTR following transfusion between dogs of either the same or different Turkish breeds was considerable. Although few dogs are transfused ≥4 days after the first transfusion, we recommend that (1) all donors and recipients be typed for DEA 1.1, (2) DEA 1.1-negative recipients receive only DEA 1.1-negative blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Only a few studies have reported the risk for sensitization of an acute transfusional reaction. In 4 native breeds of Turkey a high sensitization risk after the first transfusion (14.4–35.6%) and the risk of an acute hemolytic reaction after second transfusion (7.2–25.3%) were found [32]. In Ibizan Hound and Galgos from Spain the sensitization risk after the first transfusion was similar to the data reported here [4, 30].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Only a few studies have reported the risk for sensitization of an acute transfusional reaction. In 4 native breeds of Turkey a high sensitization risk after the first transfusion (14.4–35.6%) and the risk of an acute hemolytic reaction after second transfusion (7.2–25.3%) were found [32]. In Ibizan Hound and Galgos from Spain the sensitization risk after the first transfusion was similar to the data reported here [4, 30].…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence for DEA 1 positive dogs found in this study was very similar to results 553/890 (62.0%) reported in another study carried out in Italy [29]. Furthermore, there have been other studies that showed similar results for DEA 1 positive dogs as in the case of Nigeria 71/178 (60.1%), Turkey 116/178 (65.2%), Portugal 156/274 (56.9%), and Spain 110/206 (53.4%) [4, 25, 28, 32]. Nevertheless, the first research about blood groups distribution in dogs from 1961 reported a lower prevalence of DEA 1 positive dogs 148/332 (44.6%) [13].…”
Section: Discussionmentioning
confidence: 54%
“…The risk for sensitisation after first-time transfusion of untyped blood was found to be considerable but lower than that reported earlier from elsewhere (Ekiz et al . 2011 ; Ferreira et al . 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…DEA 1.1 is expressed in approximately 40–60 per cent of the general canine population. However, marked differences in DEA 1.1 frequencies among breeds and geographic locations have been reported (Novais and others 1999, van der Merwe and others 2002, Nottidge and others 2006, Gracner and others 2007, Hale and others 2008, Zubcic and others 2008, Iazbik and others 2010, Ergul Ekiz and others 2011, Ferreira and others 2011). …”
Section: Introductionmentioning
confidence: 98%